cat theory tweaks
authorJim Pryor <profjim@jimpryor.net>
Tue, 2 Nov 2010 13:00:49 +0000 (09:00 -0400)
committerJim Pryor <profjim@jimpryor.net>
Tue, 2 Nov 2010 13:00:49 +0000 (09:00 -0400)
Signed-off-by: Jim Pryor <profjim@jimpryor.net>
advanced_topics/monads_in_category_theory.mdwn

index 29b6feb..044d973 100644 (file)
@@ -173,7 +173,7 @@ I'll assert without proving that vertical composition is associative and has an
 
 <pre>
        (&phi; -h- &eta;)[C1]  =  L(&eta;[C1]) &#8728; &psi;[G(C1)]
-                                 =  &psi;[H(C1)] &#8728; K(&eta;[C1])
+                                  =  &psi;[H(C1)] &#8728; K(&eta;[C1])
 </pre>
 
 Horizontal composition is also associative, and has the same identity as vertical composition.
@@ -186,7 +186,7 @@ In earlier days, these were also called "triples."
 
 A **monad** is a structure consisting of an (endo)functor `M` from some category <b>C</b> to itself, along with some natural transformations, which we'll specify in a moment.
 
-Let `T` be a set of natural transformations `p`, each being between some (variable) functor `P` and another functor which is the composite `MP'` of `M` and a (variable) functor `P'`. That is, for each element `C1` in <b>C</b>, `p` assigns `C1` a morphism from element `P(C1)` to element `MP'(C1)`, satisfying the constraints detailed in the previous section. For different members of `T`, the relevant functors may differ; that is, `p` is a transformation from functor `P` to `MP'`, `q` is a transformation from functor `Q` to `MQ'`, and none of `P`, `P'`, `Q`, `Q'` need be the same.
+Let `T` be a set of natural transformations <code>&phi;</code>, each being between some (variable) functor `F` and another functor which is the composite `MF'` of `M` and a (variable) functor `F'`. That is, for each element `C1` in <b>C</b>, <code>&phi;</code> assigns `C1` a morphism from element `F(C1)` to element `MF'(C1)`, satisfying the constraints detailed in the previous section. For different members of `T`, the relevant functors may differ; that is, <code>&phi;</code> is a transformation from functor `F` to `MF'`, <code>&gamma;</code> is a transformation from functor `G` to `MG'`, and none of `F`, `F'`, `G`, `G'` need be the same.
 
 One of the members of `T` will be designated the "unit" transformation for `M`, and it will be a transformation from the identity functor `1C` for <b>C</b> to `M(1C)`. So it will assign to `C1` a morphism from `C1` to `M(C1)`.
 
@@ -194,50 +194,52 @@ We also need to designate for `M` a "join" transformation, which is a natural tr
 
 These two natural transformations have to satisfy some constraints ("the monad laws") which are most easily stated if we can introduce a defined notion.
 
-Let `p` and `q` be members of `T`, that is they are natural transformations from `P` to `MP'` and from `Q` to `MQ'`, respectively. Let them be such that `P' = Q`. Now `(M q)` will also be a natural transformation, formed by composing the functor `M` with the natural transformation `q`. Similarly, `(join Q')` will be a natural transformation, formed by composing the natural transformation `join` with the functor `Q'`; it will transform the functor `MMQ'` to the functor `MQ'`. Now take the vertical composition of the three natural transformations `(join Q')`, `(M q)`, and `p`, and abbreviate it as follows:
+Let <code>&phi;</code> and <code>&gamma;</code> be members of `T`, that is they are natural transformations from `F` to `MF'` and from `G` to `MG'`, respectively. Let them be such that `F' = G`. Now `(M &gamma;)` will also be a natural transformation, formed by composing the functor `M` with the natural transformation <code>&gamma;</code>. Similarly, `(join G')` will be a natural transformation, formed by composing the natural transformation `join` with the functor `G'`; it will transform the functor `MMG'` to the functor `MG'`. Now take the vertical composition of the three natural transformations `(join G')`, <code>(M &gamma;)</code>, and <code>&phi;</code>, and abbreviate it as follows:
 
-       q <=< p  =def.  ((join Q') -v- (M q) -v- p)
+<pre>
+       &gamma; <=< &phi;  =def.  ((join G') -v- (M &gamma;) -v- &phi;)
+</pre>
 
 Since composition is associative I don't specify the order of composition on the rhs.
 
-In other words, `<=<` is a binary operator that takes us from two members `p` and `q` of `T` to a composite natural transformation. (In functional programming, at least, this is called the "Kleisli composition operator". Sometimes its written `p >=> q` where that's the same as `q <=< p`.)
+In other words, `<=<` is a binary operator that takes us from two members <code>&phi;</code> and <code>&gamma;</code> of `T` to a composite natural transformation. (In functional programming, at least, this is called the "Kleisli composition operator". Sometimes its written <code>&phi; >=> &gamma;</code> where that's the same as <code>&gamma; <=< &phi;</code>.)
 
-`p` is a transformation from `P` to `MP'` which = `MQ`; `(M q)` is a transformation from `MQ` to `MMQ'`; and `(join Q')` is a transformation from `MMQ'` to `MQ'`. So the composite `q <=< p` will be a transformation from `P` to `MQ'`, and so also eligible to be a member of `T`.
+&phi; is a transformation from `F` to `MF'` which = `MG`; `(M &gamma;)` is a transformation from `MG` to `MMG'`; and `(join G')` is a transformation from `MMG'` to `MG'`. So the composite &gamma; <=< &phi; will be a transformation from `F` to `MG'`, and so also eligible to be a member of `T`.
 
 Now we can specify the "monad laws" governing a monad as follows:
 
        (T, <=<, unit) constitute a monoid
 
-That's it. (Well, perhaps we're cheating a bit, because `q <=< p` isn't fully defined on `T`, but only when `P` is a functor to `MP'` and `Q` is a functor from `P'`. But wherever `<=<` is defined, the monoid laws are satisfied:
+That's it. (Well, perhaps we're cheating a bit, because &gamma; <=< &phi; isn't fully defined on `T`, but only when `F` is a functor to `MF'` and `G` is a functor from `F'`. But wherever `<=<` is defined, the monoid laws are satisfied:
 
-       (i) q <=< p is also in T
-       (ii) (r <=< q) <=< p  =  r <=< (q <=< p)
-       (iii.1) unit <=< p  =  p                 (here p has to be a natural transformation to M(1C))
-       (iii.2)                p  =  p <=< unit  (here p has to be a natural transformation from 1C)
+       (i) &gamma; <=< &phi; is also in T
+       (ii) (&rho; <=< &gamma;) <=< &phi;  =  &rho; <=< (&gamma; <=< &phi;)
+       (iii.1) unit <=< &phi;  =  &phi;                 (here &phi; has to be a natural transformation to M(1C))
+       (iii.2)                &phi;  =  &phi; <=< unit  (here &phi; has to be a natural transformation from 1C)
 
-If `p` is a natural transformation from `P` to `M(1C)` and `q` is `(p Q')`, that is, a natural transformation from `PQ` to `MQ`, then we can extend (iii.1) as follows:
+If &phi; is a natural transformation from `F` to `M(1C)` and &gamma; is `(&phi; G')`, that is, a natural transformation from `PG` to `MG`, then we can extend (iii.1) as follows:
 
-       q = (p Q')
-         = ((unit <=< p) Q')
-         = ((join -v- (M unit) -v- p) Q')
-         = (join Q') -v- ((M unit) Q') -v- (p Q')
-         = (join Q') -v- (M (unit Q')) -v- q
+       &gamma; = (&phi; G')
+         = ((unit <=< &phi;) G')
+         = ((join -v- (M unit) -v- &phi;) G')
+         = (join G') -v- ((M unit) G') -v- (&phi; G')
+         = (join G') -v- (M (unit G')) -v- &gamma;
          ??
-         = (unit Q') <=< q
+         = (unit G') <=< &gamma;
 
-where as we said `q` is a natural transformation from some `PQ'` to `MQ'`.
+where as we said &gamma; is a natural transformation from some `PG'` to `MG'`.
 
-Similarly, if `p` is a natural transformation from `1C` to `MP'`, and `q` is `(p Q)`, that is, a natural transformation from `Q` to `MP'Q`, then we can extend (iii.2) as follows:
+Similarly, if &phi; is a natural transformation from `1C` to `MF'`, and &gamma; is `(&phi; G)`, that is, a natural transformation from `G` to `MF'G`, then we can extend (iii.2) as follows:
 
-       q = (p Q)
-         = ((p <=< unit) Q)
-         = (((join P') -v- (M p) -v- unit) Q)
-         = ((join P'Q) -v- ((M p) Q) -v- (unit Q))
-         = ((join P'Q) -v- (M (p Q)) -v- (unit Q))
+       &gamma; = (&phi; G)
+         = ((&phi; <=< unit) G)
+         = (((join F') -v- (M &phi;) -v- unit) G)
+         = ((join F'G) -v- ((M &phi;) G) -v- (unit G))
+         = ((join F'G) -v- (M (&phi; G)) -v- (unit G))
          ??
-         = q <=< (unit Q)
+         = &gamma; <=< (unit G)
 
-where as we said `q` is a natural transformation from `Q` to some `MP'Q`.
+where as we said &gamma; is a natural transformation from `G` to some `MF'G`.
 
 
 
@@ -264,67 +266,67 @@ Recall that join is a natural transformation from the (composite) functor MM to
 
        (1) join[b] &#8728; MM(f)  =  M(f) &#8728; join[a]
 
-Next, consider the composite transformation ((join MQ') -v- (MM q)).
-       q is a transformation from Q to MQ', and assigns elements C1 in <b>C</b> a morphism q*: Q(C1) &rarr; MQ'(C1). (MM q) is a transformation that instead assigns C1 the morphism MM(q*).
-       (join MQ') is a transformation from MMMQ' to MMQ' that assigns C1 the morphism join[MQ'(C1)].
+Next, consider the composite transformation ((join MG') -v- (MM &gamma;)).
+       &gamma; is a transformation from G to MG', and assigns elements C1 in <b>C</b> a morphism &gamma;*: G(C1) &rarr; MG'(C1). (MM &gamma;) is a transformation that instead assigns C1 the morphism MM(&gamma;*).
+       (join MG') is a transformation from MMMG' to MMG' that assigns C1 the morphism join[MG'(C1)].
        Composing them:
-       (2) ((join MQ') -v- (MM q)) assigns to C1 the morphism join[MQ'(C1)] &#8728; MM(q*).
+       (2) ((join MG') -v- (MM &gamma;)) assigns to C1 the morphism join[MG'(C1)] &#8728; MM(&gamma;*).
 
-Next, consider the composite transformation ((M q) -v- (join Q)).
-       (3) This assigns to C1 the morphism M(q*) &#8728; join[Q(C1)].
+Next, consider the composite transformation ((M &gamma;) -v- (join G)).
+       (3) This assigns to C1 the morphism M(&gamma;*) &#8728; join[G(C1)].
 
 So for every element C1 of <b>C</b>:
-       ((join MQ') -v- (MM q))[C1], by (2) is:
-       join[MQ'(C1)] &#8728; MM(q*), which by (1), with f=q*: Q(C1)&rarr;MQ'(C1) is:
-       M(q*) &#8728; join[Q(C1)], which by 3 is:
-       ((M q) -v- (join Q))[C1]
+       ((join MG') -v- (MM &gamma;))[C1], by (2) is:
+       join[MG'(C1)] &#8728; MM(&gamma;*), which by (1), with f=&gamma;*: G(C1)&rarr;MG'(C1) is:
+       M(&gamma;*) &#8728; join[G(C1)], which by 3 is:
+       ((M &gamma;) -v- (join G))[C1]
 
-So our (lemma 1) is: ((join MQ') -v- (MM q))  =  ((M q) -v- (join Q)), where q is a transformation from Q to MQ'.
+So our (lemma 1) is: ((join MG') -v- (MM &gamma;))  =  ((M &gamma;) -v- (join G)), where &gamma; is a transformation from G to MG'.
 
 
 Next recall that unit is a natural transformation from 1C to M. So for elements C1 in <b>C</b>, unit[C1] will be a morphism from C1 to M(C1). And for any morphism f:a&rarr;b in <b>C</b>:
        (4) unit[b] &#8728; f = M(f) &#8728; unit[a]
 
-Next consider the composite transformation ((M q) -v- (unit Q)). (5) This assigns to C1 the morphism M(q*) &#8728; unit[Q(C1)].
+Next consider the composite transformation ((M &gamma;) -v- (unit G)). (5) This assigns to C1 the morphism M(&gamma;*) &#8728; unit[G(C1)].
 
-Next consider the composite transformation ((unit MQ') -v- q). (6) This assigns to C1 the morphism unit[MQ'(C1)] &#8728; q*.
+Next consider the composite transformation ((unit MG') -v- &gamma;). (6) This assigns to C1 the morphism unit[MG'(C1)] &#8728; &gamma;*.
 
 So for every element C1 of <b>C</b>:
-       ((M q) -v- (unit Q))[C1], by (5) =
-       M(q*) &#8728; unit[Q(C1)], which by (4), with f=q*: Q(C1)&rarr;MQ'(C1) is:
-       unit[MQ'(C1)] &#8728; q*, which by (6) =
-       ((unit MQ') -v- q)[C1]
+       ((M &gamma;) -v- (unit G))[C1], by (5) =
+       M(&gamma;*) &#8728; unit[G(C1)], which by (4), with f=&gamma;*: G(C1)&rarr;MG'(C1) is:
+       unit[MG'(C1)] &#8728; &gamma;*, which by (6) =
+       ((unit MG') -v- &gamma;)[C1]
 
-So our lemma (2) is: (((M q) -v- (unit Q))  =  ((unit MQ') -v- q)), where q is a transformation from Q to MQ'.
+So our lemma (2) is: (((M &gamma;) -v- (unit G))  =  ((unit MG') -v- &gamma;)), where &gamma; is a transformation from G to MG'.
 
 
-Finally, we substitute ((join Q') -v- (M q) -v- p) for q <=< p in the monad laws. For simplicity, I'll omit the "-v-".
+Finally, we substitute ((join G') -v- (M &gamma;) -v- &phi;) for &gamma; <=< &phi; in the monad laws. For simplicity, I'll omit the "-v-".
 
-       for all p,q,r in T, where p is a transformation from P to MP', q is a transformation from Q to MQ', R is a transformation from R to MR', and P'=Q and Q'=R:
+       for all &phi;,&gamma;,&rho; in T, where &phi; is a transformation from F to MF', &gamma; is a transformation from G to MG', R is a transformation from R to MR', and F'=G and G'=R:
 
-       (i) q <=< p etc are also in T
+       (i) &gamma; <=< &phi; etc are also in T
        ==>
-       (i') ((join Q') (M q) p) etc are also in T
+       (i') ((join G') (M &gamma;) &phi;) etc are also in T
 
 
-       (ii) (r <=< q) <=< p  =  r <=< (q <=< p)
+       (ii) (&rho; <=< &gamma;) <=< &phi;  =  &rho; <=< (&gamma; <=< &phi;)
        ==>
-                (r <=< q) is a transformation from Q to MR', so:
-                       (r <=< q) <=< p becomes: (join R') (M (r <=< q)) p
-                                                       which is: (join R') (M ((join R') (M r) q)) p
+                (&rho; <=< &gamma;) is a transformation from G to MR', so:
+                       (&rho; <=< &gamma;) <=< &phi; becomes: (join R') (M (&rho; <=< &gamma;)) &phi;
+                                                       which is: (join R') (M ((join R') (M &rho;) &gamma;)) &phi;
                        substituting in (ii), and helping ourselves to associativity on the rhs, we get:
 
-            ((join R') (M ((join R') (M r) q)) p) = ((join R') (M r) (join Q') (M q) p)
+            ((join R') (M ((join R') (M &rho;) &gamma;)) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
                      ---------------------
                        which by the distributivity of functors over composition, and helping ourselves to associativity on the lhs, yields:
                     ------------------------
-            ((join R') (M join R') (MM r) (M q) p) = ((join R') (M r) (join Q') (M q) p)
+            ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
                                                              ---------------
-                       which by lemma 1, with r a transformation from Q' to MR', yields:
+                       which by lemma 1, with &rho; a transformation from G' to MR', yields:
                                                              -----------------
-            ((join R') (M join R') (MM r) (M q) p) = ((join R') (join MR') (MM r) (M q) p)
+            ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (join MR') (MM &rho;) (M &gamma;) &phi;)
 
-                       which will be true for all r,q,p just in case:
+                       which will be true for all &rho;,&gamma;,&phi; just in case:
 
              ((join R') (M join R')) = ((join R') (join MR')), for any R'.
 
@@ -333,37 +335,37 @@ Finally, we substitute ((join Q') -v- (M q) -v- p) for q <=< p in the monad laws
        (ii') (join (M join)) = (join (join M))
 
 
-       (iii.1) (unit P') <=< p  =  p
+       (iii.1) (unit F') <=< &phi;  =  &phi;
        ==>
-                       (unit P') is a transformation from P' to MP', so:
-                               (unit P') <=< p becomes: (join P') (M unit P') p
-                                                  which is: (join P') (M unit P') p
+                       (unit F') is a transformation from F' to MF', so:
+                               (unit F') <=< &phi; becomes: (join F') (M unit F') &phi;
+                                                  which is: (join F') (M unit F') &phi;
                                substituting in (iii.1), we get:
-                       ((join P') (M unit P') p) = p
+                       ((join F') (M unit F') &phi;) = &phi;
 
-                       which will be true for all p just in case:
+                       which will be true for all &phi; just in case:
 
-                ((join P') (M unit P')) = the identity transformation, for any P'
+                ((join F') (M unit F')) = the identity transformation, for any F'
 
                        which will in turn be true just in case:
 
        (iii.1') (join (M unit) = the identity transformation
 
 
-       (iii.2) p  =  p <=< (unit P)
+       (iii.2) &phi;  =  &phi; <=< (unit F)
        ==>
-                       p is a transformation from P to MP', so:
-                               unit <=< p becomes: (join P') (M p) unit
+                       &phi; is a transformation from F to MF', so:
+                               unit <=< &phi; becomes: (join F') (M &phi;) unit
                                substituting in (iii.2), we get:
-                       p = ((join P') (M p) (unit P))
+                       &phi; = ((join F') (M &phi;) (unit F))
                                                   --------------
                                which by lemma (2), yields:
                             ------------
-                       p = ((join P') ((unit MP') p)
+                       &phi; = ((join F') ((unit MF') &phi;)
 
-                               which will be true for all p just in case:
+                               which will be true for all &phi; just in case:
 
-               ((join P') (unit MP')) = the identity transformation, for any P'
+               ((join F') (unit MF')) = the identity transformation, for any F'
 
                                which will in turn be true just in case:
 
@@ -372,9 +374,9 @@ Finally, we substitute ((join Q') -v- (M q) -v- p) for q <=< p in the monad laws
 
 Collecting the results, our monad laws turn out in this format to be:
 
-       when p a transformation from P to MP', q a transformation from P' to MQ', r a transformation from Q' to MR' all in T:
+       when &phi; a transformation from F to MF', &gamma; a transformation from F' to MG', &rho; a transformation from G' to MR' all in T:
 
-       (i') ((join Q') (M q) p) etc also in T
+       (i') ((join G') (M &gamma;) &phi;) etc also in T
 
        (ii') (join (M join)) = (join (join M))
 
@@ -406,14 +408,14 @@ The composite morphisms said here to be identical are morphisms from the type C1
 
 In functional programming, instead of working with natural transformations we work with "monadic values" and polymorphic functions "into the monad" in question.
 
-For an example of the latter, let p be a function that takes arguments of some (schematic, polymorphic) type C1 and yields results of some (schematic, polymorphic) type M(C2). An example with M being the list monad, and C2 being the tuple type schema int * C1:
+For an example of the latter, let &phi; be a function that takes arguments of some (schematic, polymorphic) type C1 and yields results of some (schematic, polymorphic) type M(C2). An example with M being the list monad, and C2 being the tuple type schema int * C1:
 
-       let p = fun c &rarr; [(1,c), (2,c)]
+       let &phi; = fun c &rarr; [(1,c), (2,c)]
 
-p is polymorphic: when you apply it to the int 0 you get a result of type "list of int * int": [(1,0), (2,0)]. When you apply it to the char 'e' you get a result of type "list of int * char": [(1,'e'), (2,'e')].
+&phi; is polymorphic: when you apply it to the int 0 you get a result of type "list of int * int": [(1,0), (2,0)]. When you apply it to the char 'e' you get a result of type "list of int * char": [(1,'e'), (2,'e')].
 
-However, to keep things simple, we'll work instead with functions whose type is settled. So instead of the polymorphic p, we'll work with (p : C1 &rarr; M(int * C1)). This only accepts arguments of type C1. For generality, I'll talk of functions with the type (p : C1 &rarr; M(C1')), where we assume that C1' is a function of C1.
+However, to keep things simple, we'll work instead with functions whose type is settled. So instead of the polymorphic &phi;, we'll work with (&phi; : C1 &rarr; M(int * C1)). This only accepts arguments of type C1. For generality, I'll talk of functions with the type (&phi; : C1 &rarr; M(C1')), where we assume that C1' is a function of C1.
 
-A "monadic value" is any member of a type M(C1), for any type C1. For example, a list is a monadic value for the list monad. We can think of these monadic values as the result of applying some function (p : C1 &rarr; M(C1')) to an argument of type C1.
+A "monadic value" is any member of a type M(C1), for any type C1. For example, a list is a monadic value for the list monad. We can think of these monadic values as the result of applying some function (&phi; : C1 &rarr; M(C1')) to an argument of type C1.